STRUCTURE OF THE COMPUTER MODULE OF THE KDAM PROGRAM FOR DETERMINING KINEMATIC AND DYNAMIC PARAMETERS OF THE INPUT LINK - SHCHERBAN, VOLODYMYR; SHILINGOV, SERGEY; LUKASHEV, ANDREW; KOLISKO, OKSANA; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The development of the computer module of the KDAM program for determining the kinematic and dynamic parameters of the input link of the mechanisms of light industry machines allows to determine the coordinates, projections of speeds and accelerations of the center of mass of the crank and the point of attachment of the links of the Asura groups. During the dynamic analysis of the operation of the input link, the projections of the full reaction in the hinge of the input link are determined. The obtained results are used in the program to assess the intensity of technological processes of the light and textile industry when determining the change in the relative tension of the thread in the filling zones on the technological equipment. Lever mechanisms are widely used in light and textile industry machines. The working bodies of the lever mechanisms come into contact with the threads during operation. Depending on the trajectory of the movement, the angle of coverage of the working bodies of the mechanisms of the light and textile industry machines changes. A change in the value of the angle of coverage leads to a change in the tension of the threads. When the coverage angle increases to critical values, the thread may break and the technological equipment may stop. The tension of the thread increases when moving through the refueling zones of the thread feeding system on the technological equipment. This increase is due to the interaction of the thread with the guides and tension devices. The maximum tension value will be in front of the working area. A sharp increase in tension leads to a violation of the normal course of the technological process of thread processing. The development of new schemes of the thread feeding system requires an operational assessment of the value of the tension in front of the working zone. The development of special computer programs for determining the tension in the working area makes it possible to determine the necessary technological parameters. The objective function in the tasks of optimization of technological processes is the minimum necessary tension. The variable parameter in the objective function is the sum of the angles of coverage of the working bodies by the thread. The use of a computer program allows you to determine the tension and change in relative tension in the filling zones of technological machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process. Computer determination of kinematic and dynamic parameters of flat mechanisms allows to determine the parameters used in determining the intensity of technological processes. The study of the influence of the design of the thread tension device on the conditions of its interaction with the thread, taking into account its unevenness in the diameter of the cross section, is important in determining the thread tension. The tension of the thread increases when moving through the refueling zones of the thread feeding system on the technological equipment.